Recomendaciones para la Detección y Mitigación de la Marchitez del Laurel en Árboles de Aguacates y Especies Relacionadas en Jardines y Patios Hogareños - Jonathan Henry Crane; Jeff Wasielewski; Daniel Carrillo; Romina Gazis; Bruce Schaffer; Fredy Ballen; Edward Evans; Rubén Regalado (EDIS)
This is the Spanish translation of HS1358, Recommendations for the Detection and Mitigation of Laurel Wilt Disease in Avocado and Related Tree Species in the Home Landscape. Avocado trees are a popular choice for homeowners in Florida, with over 600,000 growing in Florida home landscapes. However, avocado trees as well as others in the Lauraceae family are susceptible to laurel wilt disease, which can kill a tree in as few as three weeks. This new 8-page publication of the UF/IFAS Horticultural Sciences Department provides home owners recommendations for identifying and mitigating laurel wilt disease in the home landscape. Written by Jonathan H. Crane, Jeff Wasielewski, Daniel Carrillo, Romina Gazis, Bruce Schaffer, Fredy Ballen, and Edwards Evans. https://edis.ifas.ufl.edu/hs1384